Design for Synchronized Flow Manufacturing - Ahmadi, Reza H.; Wurgaft, Herman (Management Science, 1994)
Firms that build flexibility into their manufacturing system gain a competitive edge from their ability to efficiently produce a mid-variety of products at mid-volumes. In order to realize the competitive edge of flexible systems, manufacturing management has to deal effectively with the greater complexity that flexibility brings about. One of the key factors for the success of a flexible system is the management of the product set flow. If the product flow is poorly managed, products may have long manufacturing lead times, and materials may spend a large amount of time in queues as work in process. In such a situation, most of the competitive potential of the flexible system may be lost. But if the flow of materials through the production/assembly stations is carefully synchronized, with materials moving smoothly and continuously from one operation to the next, then it is possible to attain short manufacturing lead times and little waiting. We refer to this operating condition as synchronized flow. In this paper, we study how to attain a synchronized flow for product sets with different characteristics regarding process flexibility and consistency.